2019
DOI: 10.2174/1872211313666190306160116
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Cocrystal: A Novel Approach to Tailor the Biopharmaceutical Properties of a Poorly Water Soluble Drug

Abstract: Background: The present study reports the formation of a cocrystal of candesartan with the coformer methyl paraben, its characterization and determination of its bioavailability. Candesartan is a poorly water-soluble drug having an anti-hypertensive activity. The recent patents on the cocrystals of the drugs Progesterone (US9982007B2), Epalrestat (EP2326632B1), Gefitinib (WO2015170345A1), and Valsartan (CN102702118B) for enhancement of solubility, helped in selection of the drug for this work. Methods: Cande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In fact, several technological innovations developed to increase candesartan solubility have demonstrated to increase drug bioavailability. The formation of co-crystals improved the drug bioavailability in Wistar rats [31] and nanosized suspensions with higher saturation solubility showed improved bioavailability in a murine model [32]. Candesartan loaded proniosomes showed faster dissolution and higher bioavailability after oral administration in rats [5].…”
Section: Discussionmentioning
confidence: 95%
“…In fact, several technological innovations developed to increase candesartan solubility have demonstrated to increase drug bioavailability. The formation of co-crystals improved the drug bioavailability in Wistar rats [31] and nanosized suspensions with higher saturation solubility showed improved bioavailability in a murine model [32]. Candesartan loaded proniosomes showed faster dissolution and higher bioavailability after oral administration in rats [5].…”
Section: Discussionmentioning
confidence: 95%
“…[8] Similarly, the antihypertensive drug candesartan was cocrystallized with p-MHB through solution crystallization method and characterized using PXRD, FTIR, and DSC analyses which show that it has improved solubility compared with that of the pure drug. [9] Khan et al reported that one of the antimalarial drugs Quinidine was successfully cocrystallized with p-MHB and confirmed through solid-state NMR and DFT studies that in which p-MHB is acting as a molecular hook via hydrogen bonding. [10] Similarly, the second compound selected, urea [CO(NH 2 ) 2 ], is also a well-known and highly potential material in human history assessed from the early century's and it has several applications in various industries such as agriculture, dietary technology, pharmaceutical, medicine, etc.…”
Section: Introductionmentioning
confidence: 95%
“…Nevirapine (pKa 2.8), at higher doses exhibit solubility limited absorption with low bioavailability. 7,8 It is possible to prepare novel solid forms of nevirapine with greater therapeutic efficacy and commercial value via cocrystallization. The various cocrystals of nevirapine with amides, carboxylic acid, amino acids have been reported possessing enhanced solubility and dissolution.…”
Section: Introductionmentioning
confidence: 99%